The wild river - Monty, Chris; Sterckx, Jean-Luc. ([S.l.] Blue Bird Films, 1990)
A journey at the headwaters of the ancient Nile in Subsaharan Africa. A look at the forgotten people, the Burne, the Bodi, the Toposa warriors and the Derikas in Sudan. Reveals also the volcanic terrain, hot spring and exotic wildlife.
VHS.
Editor, Didier Fassio.
Keywords: Dinka (African people) -- Social life and customs; Nile River Valley; Toposa (African people) -- Social life and customs; Africa, Sub-Saharan -- Description and travel